Relationship between language attitudes towards task-based language teaching and English language speaking performance among Malaysian polytechnic students - Tee, Wei Wong; Ismail, Lilliati (Universiti Pendidikan Sultan Idris, 2023)
Language attitude towards learning a second language is just as important as the language learning method they use. It is considered one of the essential factors which affect learners’ learning process. Despite receiving sustained academic attention from scholars, few studies have been devoted to investigating students’ language attitudes on task-based language teaching (TBLT) and its influence on students’ speaking performance. Hence, this study aimed to examine the relationship between students’ language attitudes towards TBLT and English language speaking performance. This study adopted a quasi-experimental research design. Thirty polytechnic students enrolled in the Communicative English II course participated in the study. An attitudinal questionnaire was used to gauge the students’ language attitudes towards the use of TBLT in enhancing their speaking performance and an oral presentation task was used to measure the students’ speaking performance. By using the data collected through the questionnaire and oral presentation scores, the relationship between students’ language attitudes towards TBLT and speaking performance was determined using descriptive statistics and Pearson correlation. The findings of the study showed that students demonstrated positive attitudes toward the impact of TBLT on their speaking performance. A weak positive correlation was found between students’ language attitudes toward TBLT and English language speaking performance. The findings of the study have practical implications for improving teaching practices and provide insights into the use of TBLT for teaching speaking skills.